Two-Person Neuroscience and Naturalistic Social Communication: The Role of Language and Linguistic Variables in Brain-Coupling Research - García, Adolfo M.; Ibáñez, Agustín (Frontiers in Psychiatry, 2014)
Social cognitive neuroscience (SCN) seeks to understand the brain mechanisms through which we comprehend others’ emotions and intentions in order to react accordingly. For decades, SCN has explored relevant domains by exposing individual participants to predesigned stimuli and asking them to judge their social (e.g., emotional) content. Subjects are thus reduced to detached observers of situations they play no active role in. However, the core of our social experience is construed through real-time interactions requiring the active negotiation of information with other people. To gain more relevant insights into the workings of the social brain, the incipient field of two-person neuroscience (2PN) advocates the study of brain-to-brain coupling through multi-participant experiments. In this paper, we argue that the study of online language-based communication constitutes a cornerstone of 2PN. First, we review preliminary evidence illustrating how verbal interaction may shed light on the social brain. Second, we advance methodological recommendations to design experiments within language-based 2PN. Finally, we formulate outstanding questions for future research.